Book Review: Chinese in the Post-Civil War South; a People Without a History - Thompson, C Michele (The Southern Historian, 1985)
Keywords: book.review; dept.his

Vietnam - Thompson, C Michele (Acquiring Cross-Cultural Competence: Four Stages for Students of French vol I., 1998)
Keywords: dept.his

Book Review: Chinese Acupuncture [l'Acuponcture Chinoise: La Tradition chinoise classifiée, precisée]. (Paris: Maloine, 1972). By George Soulié de Morant. Translated by Lawrence Grinnell, Claudy Jeanmougin and Maurice Leveque. Edited by Paul Zmiewski. Brookline, Mass.: Paradigm Publications, 1994. xxxii, 896 pp. $125.00. - Thompson, C. Michele (The Journal of Asian Studies, 1996)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0021911800040171/resource/name/firstPage-S0021911800040171a.jpg
Keywords: book.review; dept.his

Book Review: Sexual Attraction and Childhood Association: A Chinese Brief for Edward Westermarck. By Arthur P. Wolf. Stanford, Calif.: Stanford University Press, 1995. xxiii, 561 pp. $65.00. - Thompson, C. Michele (The Journal of Asian Studies, 1996)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS002191180002934X/resource/name/firstPage-S002191180002934Xa.jpg
Keywords: book.review; dept.his

Book Review: Essays Into Vietnamese Pasts. Edited by K. W. Taylor and John K. Whitmore. Ithaca, N.Y.: Southeast Asia Program, Cornell University Press, 1995. 288 pp. $20.00 (paper). - Thompson, C. Michele (The Journal of Asian Studies, 1996)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0021911800029971/resource/name/firstPage-S0021911800029971a.jpg
Keywords: book.review; dept.his

Race and the Land in South Africa: African Challenges to Land Policy and Segregation Between 1905 and 1936. - Feinberg, Harvey M. (1999)
Keywords: dept.his; faculty_collection; sabbatical_report

[Biography of Connecticut Governor Ella T. Grasso] - Purmont, Jon E. (Fall;History., 1999)
Keywords: dept.his; faculty_collection; sabbatical_report

[Doctoral Dissertation Revision] - Kalk, Bruce H. (Fall;History., 1998)
Keywords: dept.his; faculty_collection; sabbatical_report

To Cope with a Bad Global Image: Human Rights in the People's Republic of China,1993-1994. - Lee, Ta-ling (Fall;History., 1996)
Keywords: dept.his; faculty_collection; sabbatical_report

History of the American Women's Hospitals in the early 20th century. - Quiroga, Virginia Anne Metaxas (1996)
Keywords: dept.his; faculty_collection; sabbatical_report

Land ownership, African agriculture and politics in South Africa, 1913-1939. - Feinberg, Harvey M. (1992)
Keywords: dept.his; faculty_collection; sabbatical_report

Processus Bernardi Delitiosi: The Trial of Fr. Bernard Delicieux, 3 September - 8 December 1319. - Friedlander, Alan (1991)
Keywords: dept.his; faculty_collection; sabbatical_report

Book Research and Testimony Before the House Subcommittee on International Law and Immigration and Refugees, October 2, 1991. - Hamilton-Merritt, Jane (1991)
Keywords: dept.his; faculty_collection; sabbatical_report

A Biography of Ferdinand and Isabella. - Stewart, Paul (1989)
Keywords: dept.his; faculty_collection; sabbatical_report

Leonard Bacon. - Davis, Hugh (1988)
Keywords: dept.his; faculty_collection; sabbatical_report

Failure of Democracy: Human Rights in the People's Republic of China. - Lee, Ta-ling (Spring; History., 1988)
Keywords: dept.his; faculty_collection; sabbatical_report

A Meditator's Diary: A Western Woman's Unique Experiences in Thailand Monasteries - Hamilton-Merritt, Jane (Souvenir Press, 1976)
Keywords: Buddhism; Buddhist meditations; Hamilton-Merritt; Jane; Meditation; dept.his; faculty_collection

A Meditator's Diary: A Western Woman's Unique Experiences in Thailand Temples - Hamilton-Merritt, Jane (Harper & Row, 1976)
Keywords: Buddhism; Hamilton-Merritt; Jane; Meditation; dept.his; faculty_collection

American Pacific Ocean Trade; Its Impact on Foreign Policy and Continental Expansion, 1784-1860 - Caruthers, J. Wade (Exposition Press, 1973)
Keywords: Commerce; History; History; Pacific Area; History; United States; Pacific Area; United States; dept.his; faculty_collection

Walter Reuther, - Tyler, Robert L. (W. B. Eerdmans, 1973)
Keywords: Reuther; Walter; 1907-1970; dept.his; faculty_collection

The History of Kenya Agriculture. - Cone, L. Winston; Lipscomb, J. F. (University Press of Africa, 1972)
Keywords: Agriculture; History; Kenya; dept.his; faculty_collection

The Revenge of Heaven; Journal of a Young Chinese. - Ling, Ken; London, Miriam; Lee, Ta-ling (Putnam, 1972)
Keywords: 1949-; China; Politics and government; dept.his; faculty_collection

American Nativism, 1830-1860 - Leonard, Ira M.; Parmet, Robert D. (Van Nostrand Reinhold, 1971)
Keywords: 1815-1861; Nativism; Immigrants; Politics and government; United States; United States; dept.his; faculty_collection

The Regulators in North Carolina: A Documentary History, 1759-1776. - Powell, William S.; Huhta, James K.; Farnham, Thomas J. (State Dept. of Archives and History, 1971)
Keywords: History; North Carolina; Regulator Insurrection; 1766-1771; Sources; dept.his; faculty_collection

Africana: Holdings of Books and Other African Resource Material in the Hilton C. Buley Library at Southern Connecticut State College - Southern Connecticut State College Library (Hilton C. Buley Library, Southern Connecticut State College, 1971)
Book Title: Africana: holdings of books and other African resource material in the Hilton C. Buley Library at Southern Connecticut State College Edition: Rev. Place: New Haven
Keywords: Africa; Bibliography; Catalogs; Africa; Connecticut; Library resources; New Haven; dept.his; faculty_collection

Gouverneur Morris and the American Revolution, - Mintz, Max M. (University of Oklahoma Press, 1970)
Report for Bachelor of Engineering (Naval Architecture)., ***CD-ROM held at loans desk***
Keywords: 1775-1783; New York (State); 1775-1783; United States; Biography; Legislators; Biography; United States; Foreign relations; History; Morris; Gouverneur; 1752-1816; Statesmen; Politics and government; Revolution; 1775-1783; dept.his; faculty_collection

Lyautey in Morocco: Protectorate Administration, 1912-1925 - Scham, Alan (University of California Press, 1970)
Keywords: Lyautey; Louis Hubert Gonzalve; 1854-1934; Morocco; Politics and government; dept.his; faculty_collection

Rebels of the Woods; the I.W.W. in the Pacific Northwest, - Tyler, Robert L. (University of Oregon Books, 1967)
Keywords: Industrial Workers of the World; dept.his; faculty_collection

Kenya Women Look Ahead - Oloo, Celina Nyai; Cone, Virginia S. (East African Literature Bureau, 1965)
Keywords: Kenya; Kenya; Social life and customs; Women; dept.his; faculty_collection

Seeds of Empire: The American Revolutionary Conquest of the Iroquois - Mintz, Max M. (University, 1999)
"The American Revolution was a struggle not only for independence, but for the lands of Native Americans. The jewel in this conflict was the upstate New York domain of the Iroquois Six Nations, where fertile river valleys were a magnet for farmers weary of New England's stubborn soil." "While at first intentionally neutral, the Iroquois were soon forced to choose sides between either rebel or British forces. Seeds of Empire recreates the events surrounding General John Sullivan's scorched-earth campaign against the Six Nations of the American Indians of New York and the Eastern territories in 1779, following the surrender of General John Burgoyne's entire British army at the Battle of Saratoga. Abandoned by both the rebels and the British at the end of the revolution and devastated by the ravages of war, the Iroquois found themselves powerless to resist the post-Revolutionary takeover and peopling of their heartland by the new American nation."–Jacket.
Keywords: Sullivan's Indian Campaign; 1779; dept.his; faculty_collection

Leonard Bacon: New England Reformer and Antislavery Moderate - Davis, Hugh (Louisiana State University Press, 1998)
A nationally powerful reformer, editor, church leader, and author, Leonard Bacon (1802-1881) influenced the thinking of northern Protestants for more than fifty years. In this detailed biography, Hugh Davis offers the first scholarly treatment of Bacon's life and work. Convinced that he was obligated to educate the American people on a broad range of social, political, and theological issues, Bacon, a Congregational minister, actively sought to connect his church and community to the larger world of organized benevolence, religious and reform journalism, social activism, and scholarship. The son of New England Congregational missionaries to the native Americans on the Michigan frontier, he also endeavored to extend evangelical religion and New England ideas and institutions to the rest of the nation and even overseas. Offering new insights into the nineteenth-century Protestant ministry, the evangelical mentality, and the efforts of Americans in Bacon's generation to address the moral and social issues of their time, Leonard Bacon will prove an invaluable contribution to American religious, social, and political history.–(Source of description unspecified.)
SCSU Faculty Scholar Award
Keywords: Bacon; Leonard; 1802-1881; Congregational churches; Biography; Clergy; United States; award_winner; dept.his; faculty_collection

Racism Matters - Wright, W. D. (Praeger, 1998)
This work offers a discussion of racism in America focusing on how white people have been affected by their own racism and how it impacts upon relations between blacks and whites. It draws attention to how racism is different from race and shows how whites have maintained a white racist America.
Keywords: Race relations; Racism; United States; United States; dept.his; faculty_collection

A Concise History of the United States with Documents - House, Lewis; Purmont, Jon E.; Leonard, Ira M. (TLI Press, 1997)
Keywords: History; United States; dept.his; faculty_collection

Black Intellectuals, Black Cognition, and a Black Aesthetic - Wright, W. D. (Praeger, 1997)
Keywords: African American intellectuals; African Americans; Intellectual life; African American aesthetics; African Americans; Race identity; dept.his; faculty_collection

Processus Bernardi Delitiosi: The Trial of Fr. Bernard Délicieux, 3 September-8 December 1319 - Friedlander, Alan (American Philosophical Society, 1996)
Keywords: Bernard; Délicieux; frère; approximately 1260-approximately 1320; Trials; litigation; etc; dept.his; faculty_collection

Portrait of an Unknown Man: Manuel Azaña and Modern Spain - Rivas Cherif, Cipriano de; Stewart, Paul; Rivas, Enrique de (Fairleigh Dickinson University Press ; Associated University Presses, 1995)
Keywords: 1931-1939; Azaña; Manuel; 1880-1940; Presidents; Biography; Spain; Politics and government; Spain; dept.his; faculty_collection

A Concise History of the United States. - House, Lewis; Purmont, Jon E.; Leonard, Ira (TLI Press, 1994)
Keywords: History; United States; dept.his; faculty_collection

The Bamboo Gulag: Human Rights in the People's Republic of China, 1991-1992 - Lee, Ta-ling; Copper, John Franklin (University of Maryland School of Law, 1994)
Keywords: 1976-2002; China; China; China; Civil rights; Human rights; Politics and government; dept.his; faculty_collection

Tragic Mountains: The Hmong, the Americans, and the Secret Wars for Laos, 1942-1992 - Hamilton-Merritt, Jane (Indiana University Press, 1993)
Keywords: 20th century; 20th century; Laos; Government policy; History; Hmong (Asian people); Laos; Hmong (Asian people); Politics and government; Laos; Wars; Hmong (Asian people); dept.his; faculty_collection

Failure of Democracy Movement: Human Rights in the People's Republic of China, 1988/89 - Lee, Ta-ling; Copper, John Franklin (School of Law, University of Maryland, 1991)
Keywords: China; China; China; Civil rights; History; Human rights; Tiananmen Square Incident; 1989; dept.his; faculty_collection

Joshua Leavitt, Evangelical Abolitionist - Davis, Hugh (Louisiana State University Press, 1990)
Keywords: 1815-1861; United States; 19th century; United States; Biography; Antislavery movements; History; Leavitt; Joshua; 1794-1873; Abolitionists; Social conditions; To 1865; United States; United States; Evangelicalism; dept.his; faculty_collection

The Generals of Saratoga: John Burgoyne and Horatio Gates - Mintz, Max M. (Yale University Press, 1990)
Keywords: Burgoyne; John; 1722-1792; Gates; Horatio; 1728-1806; Saratoga Campaign; N.Y.; 1777; dept.his; faculty_collection

One Step Forward, One Step Back: Human Rights in the People's Republic of China in 1987/88 - Copper, John Franklin (School of Law, University of Maryland, 1989)
Keywords: 1976-2002; China; China; Human rights; Politics and government; dept.his; faculty_collection

Africans and Europeans in West Africa: Elminans and Dutchmen on the Gold Coast During the Eighteenth Century - Feinberg, Harvey M. (American Philosophical Society, 1989)
SCSU Faculty Scholar Award
Keywords: Dutch; Ghana; Elmina (Ghana); History; award_winner; dept.his; faculty_collection

Fairfield: The Biography of a Community, 1639-1989 - Farnham, Thomas J. (Published for the Fairfield Historical Society by Phoenix Pub., 1988)
Keywords: Fairfield (Conn.); History; dept.his; faculty_collection

Student Protests in Connecticut Colleges and Universities, 1701-1870: Yale College as a Case Study - Purmont, Jon Emmett (Thesis Ph. D.–Columbia University., 1988)
Keywords: Case studies; Education; Higher; Connecticut; History; History; Students; Political activity; Yale University; dept.his; faculty_collection

Reform in Reverse: Human Rights in the People's Republic of China, 1986/1987 - Lee, Ta-ling; Copper, John Franklin (School of Law, University of Maryland, 1987)
Keywords: China; Human rights; dept.his; faculty_collection

Manifest Destinies: The Usa, the Ussr - Mintz, Max M.; Bennet, John (Boston Pub. Co. ; Distributed by Field Publications, 1987)
Keywords: History; History; Russia; History; Soviet Union; United States; dept.his; faculty_collection

Upper State Street 1640-1982 - Farnham, Thomas J. (s.n., 1983)
Keywords: New Haven (Conn.); Streets; Upper State Street; dept.his; faculty_collection

Vigil in Benicarló - Azaña, Manuel (Fairleigh Dickinson University Press, 1982)
Keywords: Civil War; 1936-1939; Drama; History; Spain; dept.his; faculty_collection

Hmong and Yao: Mountain Peoples of Southeast Asia - Hamilton-Merritt, Jane (SURVIVE, 1982)
SCSU Faculty Scholar Award
Keywords: Hmong (Asian people); Yao (Southeast Asian people); Chemical warfare; award_winner; dept.his; faculty_collection

My First Days of School - Hamilton-Merritt, Jane (Simon & Schuster, 1982)
Five-year-old Kate relates the experiences of her first day in kindergarten.
Keywords: dept.his; faculty_collection

Our New Baby - Hamilton-Merritt, Jane (J. Messner, 1982)
Follows the experiences and changing feelings of a child during a year when a new baby becomes a part of his family.
Keywords: Infants; Juvenile literature; Juvenile literature; Parent and child; Juvenile literature; Siblings; dept.his; faculty_collection

Superpowers, the USA, the USSR - Mintz, Max M.; Bennet, John (HBJ Press, 1980)
Keywords: History; History; Soviet Union; United States; dept.his; faculty_collection

Weston: The Forging of a Connecticut Town - Farnham, Thomas J. (Published for the Weston Historical Society by Phoenix Pub., 1979)
Keywords: History; Weston (Conn.); dept.his; faculty_collection

Historians and Slavery: A Critical Analysis of Perspectives and Irony in American Slavery, and Other Recent Works. - Wright, W. D. (1978)
Keywords: Genovese; Eugene D.; 1930-2012; Engerman; Stanley L; Perspectives and irony in American slavery; Slavery; Historiography; United States; dept.his; faculty_collection

Urban legacy: the story of America's cities - Klebanow, Diana (New American Library, 1977)
Keywords: Cities and towns; History; United States; dept.his; faculty_collection

The nature of geography and the Schaefer-Hartshorne debate - Martin, G.J. (Reflections on Richard Hartshorne's "The nature of geography', 1989)
The tendency by geographers to cast Hartshorne as either hero or villain in modern American geography is clearly represented in this essay considering the Hartshorne-Schaefer controversy, a dispute of almost mythical proportions in the modern history of American geography. Through analysis of unpublished and published documents, the author provides us with a wealth of historical information concerning the relation between the two antagonists and the events surrounding the publication of their methodological statements. The reportage has an additional, illocutionary impact that derives from the introduction of historical specificities into the discussion of mythologized events. The description and evaluation of the events surrounding this episode in American geography, especially its portrayal of spatial analysts in the uncharacteristic role of loyal sentimentalists, will probably add fuel to the dying embers of this controversy. -from Editors
Keywords: American geography; Hartshorne; R.; Schaefer; dept.egm; geographers; historical information; illocutionary impact; methodological statement; spatial analysts; ⛔ No DOI found

Access to archives and privacy: The twenty-third international archival round table conference proceedings - Newhall, A.C. (American Archivist, 1989)
1 citations (Crossref) [2023-10-31]
Keywords: dept.his

Plenty of barbarians, but no bird's milk: The depiction of Russia in German school books, 1890-1914 - Paddock, Troy R. E. (Internationale Schulbuchforschung, 1998)
This article examines the description of Russia in German history and geography textbooks. Nineteenth-century German pedagogical theory linked the natural sciences and the human sciences; the connection supplies further evidence of the perceived organic nature of the nation-state. Although regional and confessional differences among the German states affected the description of German history, the depiction of Russia was consistent. Russia was depicted as a barbaric, backward, and Asiatic empire. The implicit, and often explicit, comparison in the texts was between Russia and Germany. The description of a foreign power served to reinforce German national identity. Moreover, an examination of German geography and history textbooks reveals striking similarities between the perception of Russia in Germany and the Anglo-French depiction of the Near East. Dieser Aufsatz befaßt sich mit dem Rußlandbild in deutschen Schulbüchern für Geschichte und Geographie. Deutsche Pädagogik im 19. Jahrhundert verband die Naturwissenschaft mit der Geisteswissenschaft; diese Verbindung ist noch ein Beweis für die Auf- fassung des Nationalstaats als organisches Wesen. Obwohl regionale und konfessionelle Unterschiede unter den deutschen Ländern die Darstellung von deutscher Geschichte beeinflußten, war die Schilderung von Rußland übereinstimmend. Rußland wurde als ein barbarisches, rückständiges, asiatisches Reich gezeichnet. Der unausgesprochene, und manchmal doch ausgesprochene Vergleich in den Büchern galt Deutschland und Rußland. Die Darstellung der fremden Macht verstärkte die deutsche Nationalidentität. Außerdem enthüllt eine Untersuchung der Schulbücher überraschende Ähnlichkeiten zwischen der deutschen Beschreibung von Rußland und den englischen und französischen Darstellungen des Nahen Osten. L'auteur de cet article analyse l'image de la Russie dans les manuels scolaires allemands d'histoire et de géographie. La pédagogie allemande du 19ème siècle faisait le lien entre les sciences naturelles et les sciences humaines; cette association fournit une preuve supplémentaire du fait que l'Etat-nation était perçu comme un organisme vivant. Alors que les différences régionales et confessionnelles existant entre les différents Etats allemands influençaient la présentation de l'histoire allemande, la description de la Russie était concordante. La Russie était dépeinte comme un empire barbare, arriéré et asiatique. La comparaison implicite, et souvent explicite des textes scolaires concernait la Russie et l'Allemagne. La représentation d'une puissance étrangère servait à renforcer l'identité allemande. En outre, l'analyse de ces manuels révèle des ressemblances étonnantes entre la perception de la Russie et les portraits français et anglais du Proche-Orient.
Keywords: dept.his; ⛔ No DOI found

Abolition and Antislavery: United States - Forbes, Robert P. (A Historical Guide to World Slavery, 1998)
Eminent scholars provide an overview of what we now know about slavery as an institution and way of life in cultures around the globe from ancient times to the present day. Drawing on the virtual explosion of empirical research and theoretical discussion on the subject over the past thirty years, many of the articles overturn conventional wisdom and illuminate little-known aspects of the subject, with essays on topics such as concubinage, eunuchs, and occupational mobility.
Keywords: dept.his

Slavery and the Evangelical Enlightenment - Forbes, Robert Pierce (Religion and the Antebellum Debate Over Slavery, 1998)
Keywords: 19th century; 19th century; Slavery; History; History / United States / 19th Century; Slavery and the church; Social Science / Ethnic Studies / African American Studies; Social Science / Sociology of Religion; United States; dept.his; faculty_collection

Francis Kernan: The Life and Times of a 19th Century, Citizen-Politician of Upstate New York - Kernan, Karen Clemens; Kernan, John Devereux; Forbes, Robert P. (Oneida County Historical Society, 1999)
Keywords: dept.his

Eliade, Joyce, and the Terror of History - Forbes, Robert P. (CrossCurrents, 1986)
Keywords: dept.his; ⛔ No DOI found

Socio/Psycholinguistics of the cultural revolution: an empirical study - London, Ivan D.; Lee, Ta-Ling (Psychological Reports, 1977)
2 citations (Crossref) [2023-10-31] Citation Key Alias: pop00127 tex.type: [object Object]
Keywords: dept.his

Review of Desperate Diplomacy: William H. Seward's Foreign Policy, 1861 - Farnham, Thomas J. (The Journal of Southern History, 1977)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1977DR88500029 tex.unique-id: [object Object]
Keywords: dept.his

War and Government in Habsburg Spain, 1560-1620 - Thompson,iaa - Stewart, P (American Historical Review, 1977)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1977DY89600114
Keywords: dept.his

Book Review: E. J. Murphy, History of African Civilization. New York, Crowell, 1972, pp. 430, xxlv, maps, plates, $ 14.35 - Cone, L. Winston (Journal of Asian and African Studies, 1975)
"E. J. Murphy, History of African Civilization. New York, Crowell, 1972, pp. 430, xxlv, maps, plates, $ 14.35" published on 01 Jan 1975 by Brill.
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1975BS51300013, lens.org/075-687-014-811-491, pop00255 tex.type: [object Object] tex.unique-id: [object Object]
Keywords: book.review; dept.his

Works of Williams,r,sir - Evans,jx - Stewart, P (American Historical Review, 1973)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1973P376900037
Keywords: dept.his

Review of The Birth of Modern America, 1820-1850 - Farnham, Thomas J. (The Journal of Southern History, 1972)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1972L542200027 tex.unique-id: [object Object]
Keywords: dept.his

Devaldes,j and Origins of Spanish and Italian Reformation - Spanish - Nieto,jc - Stewart, P (American Historical Review, 1971)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1971K587500077
Keywords: dept.his

Review of The Era of Expansion: 1800-1848 - Farnham, Thomas J. (The Journal of Southern History, 1969)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1969Y436500013 tex.unique-id: [object Object]
Keywords: dept.his

Book Review: Gamaliel bailey and antislavery union. by stanley harrold. (kent: kent state university press, 1986. xvi + 301 pp. 28.00.) - Davis, Hugh (The Journal of American History, 1988)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/017-531-054-257-566 tex.type: [object Object]
Keywords: book.review; dept.his

Review of Explaining Religion: Criticism and Theory from Bodin to Freud - Ausmus, Harry J. (The American Historical Review, 1988)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1988R305800016 tex.unique-id: [object Object]
Keywords: dept.his

Review of Henry David Thoreau: A Life of the Mind, Robert D. Richardson, Jr - Caruthers, J. Wade; Richardson, Robert D. (The American Historical Review, 1987)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1987L308800157 tex.unique-id: [object Object]
Keywords: dept.his

Review of Religion in the Age of Romanticism: Studies in Early Nineteenth-Century Thought - Ausmus, Harry J. (The American Historical Review, 1986)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1986F313200044 tex.unique-id: [object Object]
Keywords: dept.his

Review of The Seven Day Circle: The History and Meaning of the Week - Ausmus, Harry J. (The American Historical Review, 1986)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1986D315000015 tex.unique-id: [object Object]
Keywords: dept.his

Research in South Africa: to know an archive - Feinberg, Harvey M (History in Africa, 1986)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/063-439-470-300-398 tex.type: [object Object]
Keywords: dept.his

Review of L'ordre du temps - Ausmus, Harry J. (The American Historical Review, 1985)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1985ASN9100005 tex.unique-id: [object Object]
Keywords: dept.his

Western religious thought - Ausmus, Harry J (Journal of the American Academy of Religion, 1982)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/075-157-295-827-36X tex.type: [object Object]
Keywords: dept.his

Review of Transcendentalism as a Social Movement, 1830-1850 - Caruthers, J. Wade (The American Historical Review, 1982)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1982PT98500167 tex.unique-id: [object Object]
Keywords: dept.his

Nuclear-weapons and the future - an unthinkable proposal - Tyler, RL (Humanist, 1982)
tex.unique-id: ISI:A1982PN18700002
Keywords: dept.his; ⛔ No DOI found

Book Review: Revolution and tradition in tientsin, 1949-1952 - lieberthal,kg - Lee, TL (American Historical Review, 1981)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1981LP78100116
Keywords: book.review; dept.his

High noon in memory lane - the superior reality of the past - Tyler, RL (Humanist, 1981)
tex.unique-id: ISI:A1981LL35600027
Keywords: dept.his; ⛔ No DOI found

An eighteenth-century case of plagiarism: william smith's A new voyage to guinea - Feinberg, Harvey M. (History in Africa, 1979)
1 citations (Crossref) [2023-10-31] Citation Key Alias: pop00173 tex.type: [object Object]
Keywords: dept.his

Nietzsche and eschatology - Ausmus, Harry J. (The Journal of Religion, 1978)
1 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1978GA15000001 tex.unique-id: [object Object]
Keywords: dept.his

Book Review: Visions of Utopia: Nashoba, Rugby, Ruskin, and the “New Communities” in Tennessee's Past. By John Egerton. (Knoxville: University of Tennessee Press, Tennessee Historical Commission, 1977. 95 pp. Maps, illustrations, more resources, and index. Paper, $3.50.) - Caruthers, J. Wade (Journal of American History, 1978)
J. Wade Caruthers; Visions of Utopia: Nashoba, Rugby, Ruskin, and the “New Communities” in Tennessee's Past. By John Egerton. (Knoxville: University of Tenness
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1978FQ74200055 tex.unique-id: [object Object]
Keywords: book.review; dept.his

Review of The Encyclopaedia Africana Dictionary of African Biography, Volume I: Ethiopia-Ghana - Feinberg, Harvey M. (The International Journal of African Historical Studies, 1978)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1978FX50100026 tex.unique-id: [object Object]
Keywords: dept.his

Plant Liberation - Struggle Against Fauna Chauvinism - Tyler, RL (Humanist, 1978)
tex.unique-id: ISI:A1978EH64300010
Keywords: dept.his; ⛔ No DOI found

Review of Trade and Economic Change on the Gold Coast, 1807-1874 - Feinberg, H.M. (The International Journal of African Historical Studies, 1977)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1977EA17900031 tex.unique-id: [object Object]
Keywords: dept.his

Schopenhauer's view of history: A note - Ausmus, Harry J. (History and Theory, 1976)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1976BQ84700003 tex.unique-id: [object Object]
Keywords: dept.his

There Was an Elmina Note, But.... - Feinberg, H.M. (The International Journal of African Historical Studies, 1976)
2 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1976DG10400005 tex.unique-id: [object Object]
Keywords: dept.his

Confessions of a Closet Househusband - Tyler, RL (Humanist, 1976)
tex.unique-id: ISI:A1976CL09000010
Keywords: dept.his; ⛔ No DOI found

Review of Akwapim Handbook - Feinberg, H. M. (The International Journal of African Historical Studies, 1975)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1975BF75200071 tex.unique-id: [object Object]
Keywords: dept.his

Boredom and Treadmill of Doing - Tyler, RL (Humanist, 1975)
tex.unique-id: ISI:A1975AW55800006
Keywords: dept.his; ⛔ No DOI found

New data on European mortality in West Africa: the Dutch on the Gold Coast, 1719-1760. - Feinberg, Harvey M (The Journal of African History, 1974)
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/047-758-033-564-756 tex.type: [object Object]
Keywords: dept.his

Review of Colonial Governors from the Fifteenth Century to the Present. A Comprehensive List - Feinberg, H. M. (The International Journal of African Historical Studies, 1973)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1973Q366200015 tex.unique-id: [object Object]
Keywords: dept.his

Consciousness Iv - or Let Us Not Envy Young - Tyler, RL (Humanist, 1972)
tex.unique-id: ISI:A1972Z026200008
Keywords: dept.his; ⛔ No DOI found

Old Siwash Is Not Our Beacon - Tyler, RL (Journal of General Education, 1972)
tex.unique-id: ISI:A1972L436800003
Keywords: dept.his; ⛔ No DOI found

Book Review: Mill town: A social history of everett, washington, from its earliest beginnings on the shores of puget sound to the tragic and infamous event known as the everett massacre. by norman h. clark. (seattle: university of washington press, 1970. x + 267 pp. illustrations, notes, and index. 7.95.) - Tyler, Robert (The Journal of American History, 1972)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/080-427-398-728-100 tex.type: [object Object]
Keywords: book.review; dept.his

Review of Benin and the Europeans 1485-1897 - Feinberg, H. M. (African Historical Studies, 1971)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1971Y060400021 tex.unique-id: [object Object]
Keywords: dept.his

Review of Trade and Politics on the Gold Coast: 1600-1720. A Study of the African Reaction to European Trade - Feinberg, H. M. (African Historical Studies, 1971)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1971Y060500019 tex.unique-id: [object Object]
Keywords: dept.his

Pornos and Prudes Unite - Tyler, RL (Humanist, 1971)
tex.unique-id: ISI:A1971Y044900011
Keywords: dept.his; ⛔ No DOI found

An Incident in Elmina-Dutch Relations, The Gold Coast (Ghana), 1739-1740 - Feinberg, H. M. (African Historical Studies, 1970)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1970Y060200006 tex.unique-id: [object Object]
Keywords: dept.his

Review of West African Trade and Coast Society: A Family Study - Feinberg, H. M. (African Historical Studies, 1970)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1970Y060200027 tex.unique-id: [object Object]
Keywords: dept.his

2-Marriage Revolving-Mate Generation-Bridging Plan to Save Marriage - Tyler, RL (Humanist, 1970)
tex.unique-id: ISI:A1970Y053400012
Keywords: dept.his; ⛔ No DOI found

Social education looks at history curriculum - 11-year view - Caruthers, J. Wade (Social Education, 1967)
tex.unique-id: ISI:A1967ZE01100001
Keywords: dept.his; ⛔ No DOI found

Book Review: Michael r. dutton, policing and punishment in china , london and new york: cambridge university press, 1992. pp. xii, 391. 74.95 (ISBN 0-521-40097-X). - Lee, Taling; Dutton, Michael R (Law and History Review, 1996)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/011-205-443-787-032 tex.type: [object Object]
Keywords: book.review; dept.his

A social history of wet nursing in America: From breast to bottle. - Metaxas, VA (Isis, 1999)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000085890500069
Keywords: dept.his

Ghaylan Al-Dimashqi: The isolation of a heretic in Islamic historiography - Judd, SC (International Journal of Middle East Studies, 1999)
7 citations (Crossref) [2023-10-31] tex.organization: Middle E Studies Assoc tex.unique-id: ISI:000080330000002 29th Annual Meeting of the Middle-East-Studies-Association, WASHINGTON, D.C., DEC 06-10, 1995
Keywords: dept.his

Book Review: War and the illiberal conscience: coker, christopher: boulder: westview press 240 pp., publication date: april 1998 - Paddock, Troy (History: Reviews of New Books, 1999)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/076-456-415-896-519 tex.type: [object Object]
Keywords: book.review; dept.his

The Carswell affair: The politics of a Supreme Court nomination in the Nixon administration - Kalk, BH (American Journal of Legal History, 1998)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/107-015-379-096-504 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.his

Book Review: Barbara Caine. English Feminism, 1780–1980 . New York: Oxford University Press. 1997. Pp. xvii, 336. 19.95 paper. ISBN 0-19-820434-5. - Beals, Polly (Albion, 1998)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/191-041-092-429-055 tex.type: [object Object]
Keywords: book.review; dept.his

Still stuck at sevastopol: the depiction of russia during the russo-japanese war and the beginning of the first world war in the german press - Paddock, Troy (German History, 1998)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/111-569-153-315-152 tex.type: [object Object]
Keywords: dept.his

The machine in the nursery: incubator technology and the origins of newborn intensive care. - Quiroga, VAM (Isis, 1997)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000071450400068
Keywords: dept.his

Revolutionary outlaws - allen,ethan and the struggle for independence on the early american frontier - bellesiles,ma - Mintz, MM (American Historical Review, 1995)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1995RJ06900100
Keywords: dept.his

South Africa and land ownership: what's in a deed? - Feinberg, Harvey M (History in Africa, 1995)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/018-416-240-180-454 tex.type: [object Object]
Keywords: dept.his

Book Review: Battles of the Revolutionary War, 1775–1781. By W. J. Wood. (Chapel Hill: Algonquin, 1990. xxxii + 315 pp. $24.95.) - Mintz, Max M. (Journal of American History, 1991)
Max M. Mintz; Battles of the Revolutionary War, 1775–1781. By W. J. Wood. (Chapel Hill: Algonquin, 1990. xxxii + 315 pp. $24.95.), Journal of American History,
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1991GF12400029 tex.unique-id: [object Object]
Keywords: book.review; dept.his

Save the babies - american public-health reform and the prevention of infant-mortality, 1850-1929 - meckel,ra - Quiroga, VAM (Journal of American History, 1991)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1991FP54300084
Keywords: dept.his; peer-reviewed

Diphtheria and medical therapy in late 19th century New York City - Quiroga, V.A.M. (New York State Journal of Medicine, 1990)
Keywords: Diphtheria; History of Medicine; 19th Cent.; Human; Intubation; Intratracheal; New York City; Portraits; Tracheotomy; article; dept.his; diphtheria; history of medicine; human; priority journal; ⛔ No DOI found

Book Review: abolitionism: A revolutionary movement, by hugh davis - Davis, Hugh (Pennsylvania Magazine of History and Biography, 1990)
Citation Key Alias: lens.org/165-049-126-830-503 tex.type: [object Object]
Keywords: book.review; dept.his; ⛔ No DOI found

Book Review: Denis Lalande, Jean II le Meingre, dit Boucicaut (1366–1421): Etude d'une biographie héroïque . (Publications romanes et françaises, 184.) Geneva: Droz, 1988. Paper. Pp. ii, 227. - Friedlander, Alan (Speculum, 1990)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/157-761-815-103-415 tex.type: [object Object]
Keywords: book.review; dept.his